Juridical Analysis of the Bankruptcy of PT Sritex Based on Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. - Firmansyah, Firmansyah; Palit, Silvester Magnus Loogman; Reba, William Hendrik (Westscience Press, 2025)
This study examines the bankruptcy of PT Sri Rejeki Isman Tbk (PT Sritex) within the framework of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UU Kepailitan). Employing a normative juridical approach, it analyzes the legal provisions, procedural implementation, and implications of the case. The findings reveal compliance with the statutory criteria for bankruptcy but also expose significant procedural inefficiencies, particularly in asset valuation and the Suspension of Debt Payment Obligations (PKPU) process. The study highlights the need for reforms to streamline court procedures, enhance transparency, and strengthen corporate governance practices. These measures are crucial for improving the effectiveness and equity of Indonesia’s bankruptcy system while safeguarding the rights of creditors and debtors.